Gensidigt lærende partnerskaber i teori og praksis: Et organisatorisk drama i to akter - Willert, Søren; Østergaard, Lars Domino; Nymand, Randi (Academic Quarter | Akademisk kvarter, 2013)
The article draws data from an action research project involving leaders and teaching staff from a large educational institution (researched part) and researchers and students from a university department (researcher part). The project strives for qualitative enhancement of teaching practice coupled with a wish to understand the enabling conditions behind such an enhancement. An ambitious project design was worked out. Facilitated action learning was chosen as a methods vehicle for bringing about the desired changes. The article’s first part (‘act’) leads up to a description of the principles on which the design was based: How may small scale action learning experiences be translated into large scale organizational learning and professional change. No funding agency could be found for financing the ambitious project design. The article’s second part (‘act’) describes the efforts spent on establishing an unfunded development-organization-within-the-educational-institution. University students filled in action learning facilitating roles while at the same time using their project experiences as study material (partnership for mutual learning). The collaboration between educational institution and university department is seen as an interesting prototype for furthering organization development in an age of economic scarcity.